Microglia exhibit a dynamic response, modulating inducible nitric oxide synthase expression and the production of pro-inflammatory cytokines during experimental cerebral malaria - Freire-Antunes, Lucas; Ornellas-Garcia, Uyla; Rangel-Ferreira, Marcos; Ribeiro-Almeida, Mônica Lucas; Carvalho, Leonardo José Moura; Daniel-Ribeiro, Cláudio Tadeu; Ribeiro-Gomes, Flávia Lima (Frontiers in Immunology, 2025)
Microglia play a fundamental role in maintaining central nervous system homeostasis by monitoring brain tissue for physical, structural, and biochemical alterations. Its involvement in the pathogenesis of various neurological disorders is well documented. However, the role of microglia in cerebral malaria, a disease associated with high mortality and long-term neurological sequelae, remains poorly understood. In this study, we utilized the classical model of experimental cerebral malaria (Plasmodium berghei ANKA-infected C57BL/6 mice) to investigate the dynamics and response of resident brain cell populations, particularly microglia, and the influx of other leukocytes during the development of experimental cerebral malaria. By employing flow cytometry and established markers for different leukocyte populations, we were able to discern and document an increase in the number of Ly6C+ T cells (CD45hiCD11b-CD3+ cells), inflammatory monocytes (CD45hiCD11b+TMEM119-CD206- cells), resident macrophages (CD45hiCD11b+TMEM119-CD206+ cells), and microglia (CD45lowCD11b+ TMEM119+CD206- cells) following infection. Moreover, our ex vivo analysis demonstrated an increment in the overall number of inflammatory monocytes, resident macrophages and microglia expressing inducible nitric oxide synthase (iNOS), in addition to those producing interleukin-1β or TNF. These findings highlight the pronounced reactivity of microglia in experimental cerebral malaria and provide valuable information on cell dynamics and immune responses in the brain.